15 Randomized double-blind placebo controlled trial of frontline maintenance vigil immunotherapy (VITAL study) in stage III/IV ovarian cancer: efficacy assessment in BRCA1/2-wt patients. (13th November 2020) - Rocconi, R; Grosen, E; Ghamande, S; Chan, J; Barve, M; Oh, J; Tewari, D; Morris, P; Stevens, E; Bottsford-Miller, J; Tang, M; Aaron, P; et al.
Abstract : Introduction: Vigil is an autologous tumor cell vaccine constructed from tumor tissue transfected with a DNA plasmid encoding GMCSF and bi-shRNA-furin thereby reducing TGFβ expression. Methods: A randomized double-blind placebo-controlled trial of Vigil was performed in advanced stage frontline (1L) Ovarian Cancer (OC) patients. Relapse-free survival (RFS), overall survival (OS), and safety were endpoints. Patients were randomized [1:1 to placebo (control group, CG) or Vigil (Vigil group, VG), 1 × 10e7 cells/dose for up to 12 doses] after complete response to 1L surgery and chemotherapy. Results: 91 patients were randomized in the per-protocol population (PP), (VG: n=46; CG: n=45). VG demonstrated no Grade 3 or 4 toxicity. From time of randomization median RFS (mRFS) for all 91 patients was favorable in the VG (HR 0.67, one-sided p 0.065). All 91 patients were tested for BRCA1/2 status. An advantage in mRFS was seen in the BRCA1/2-wt patients in VG (12.7 mo) compared to CG (8 mo), (HR 0.493, 90% CI [0.287 to 0.846], one-sided p 0.014) from time of randomization as well as OS benefit in VG (median not reached) vs. CG (41.4 mo) (HR of 0.417, 90% CI [0.202 to 0.86], p 0.02). 51% BRCA1/2-wt Vigil treated patients relapsed compared to 79% of placebo (median follow-up of 38.6 mo for PP). Homologous recombination deficiency status (HRD) and further determination of predictive biomarkers of response are underway. Conclusion: Vigil immunotherapy as 1L maintenance in Stage III/IV ovarian cancer is well tolerated and showed significant RFS clinical benefit, particularly in BRCA1/2-wt disease.